1997
DOI: 10.1002/(sici)1097-4644(19971101)67:2<231::aid-jcb8>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in C3H-10T1/2 cells: Roles of intracellular pH, protein kinase C, and the Na+/H+ antiporter

Abstract: Changes in intracellular ion concentrations have been correlated with the activation of an endogenous endonuclease and thus internucleosomal DNA cleavage during apoptosis in many cell types. We investigated whether intracellular pH could play a significant role in apoptotic initiation and progression in C3H-10T1/2 cells, a cell strain that does not exhibit double-stranded DNA cleavage during apoptosis. Protein kinase C and the Na+/H+ antiporter, known regulators of intracellular pH, also were assessed for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…These mechanisms are likely to be significant in vivo as well because intracellular acidification is known to occur during apoptosis (19)(20)(21)(22). Significant levels of apoptosis also have been observed by using a proton ionophore under conditions in which intracellular pH is clamped to 6.0 or below, but not to 6.75 (23), consistent with the pH ranges necessary for procaspase-3 autoactivation. Hyperacidification of the mitochondrial intermembrane space, where a substantial portion of the procaspase-3 pool is contained in some cell types (24), also has been demonstrated during apoptosis (25).…”
Section: The Safety Catch Modulates Procaspase-3 Vulnerability To Actmentioning
confidence: 86%
“…These mechanisms are likely to be significant in vivo as well because intracellular acidification is known to occur during apoptosis (19)(20)(21)(22). Significant levels of apoptosis also have been observed by using a proton ionophore under conditions in which intracellular pH is clamped to 6.0 or below, but not to 6.75 (23), consistent with the pH ranges necessary for procaspase-3 autoactivation. Hyperacidification of the mitochondrial intermembrane space, where a substantial portion of the procaspase-3 pool is contained in some cell types (24), also has been demonstrated during apoptosis (25).…”
Section: The Safety Catch Modulates Procaspase-3 Vulnerability To Actmentioning
confidence: 86%
“…43,44 To confirm such induction in BHK cells, we exposed these cells to 40 mM HMA for different periods of time 45 and estimated, 24 h after the start of treatment, the cell survival ratio by using a metabolic index provided by the MTT test. In these conditions, the survival rate significantly decreased with increases in exposure time and reached a mean of 6.872% at 24 h of HMA treatment (Figure 2a).…”
Section: Induction Of Apoptosis In Bhk Cells By Hmamentioning
confidence: 99%
“…We have also demonstrated here that 20 M tenidap decreased pH i by 0.12 pH unit. Boyle et al (1997) reported the clamping intracellular pH 6.75 did not induce a significant level of apoptosis of C3H-10T1/2 cells, which pH 6.0 did induce in these cells. Thus, the continuous retention of tenidap in local areas, such as in periodontal pockets, might affect gingival fibroblasts to reduce its growth through apoptosis.…”
Section: Discussionmentioning
confidence: 94%